Reproducción de Carcharhinus obscurus (Pisces: Carcharhinidae), en el Pacífico Nororiental - Villavicencio Garayzar, Carlos J (Universidad de Costa Rica, 1996)
A new nursery area in the American North Pacific was found for the dusky shark, Carcharhinus obscurus. Neonates (80-123 cm TL) and adult fernales (313-347 cm TL) with embryos are present during February-August in coastal lagoons. Sex ratio in neonates was near 1:1